PENERAPAN NON FINANCIAL PERFORMANCE MEASUREMENT DALAM UPAYA PERBAIKAN KINERJA DEPARTEMEN PRODUKSI BADAN USAHA ”X” DI SURABAYA - Chrisline Soesanto (Perpustakaan Universitas Surabaya, 2015)
Non Financial Performance Measurement be something important as through this measure are, company can reflect the achievement in the future. The purpose of this research is to know relations of causality of the problem was happening in companies and helped give recommendation. This study is focused on evaluating the implementation of the non financial performance measurement on a business entity engaged in the milling of disused plastic bottles. The satisfaction of customers is important for business entity so that a business entity can continue to survive and even flourish in this area, although many new competitors are emerging on the market. To carry out this research, first look at on the form of financial performance measurement that has been carried by a business entity, especially in the production. Then look and analyzing problems during this happened in measurement performance. From there can be analyzed and sought repair non financial performance measurement.